STRATEGI PENGEMBANGAN DAYA TARIK WISATA KAWASAN LEMBAH COLOL, KABUPATEN MANGGARAI TIMUR, PROVINSI NUSA TENGGARA TIMUR - Jehamin, Albertus; Sunarta, I Nyoman; Bhaskara, Gde Indra (JURNAL MASTER PARIWISATA; Volume 09, Nomor 02, Januari 2023DO - 10.24843/JUMPA.2023.v09.i02.p02, 2023)
Colol Valley area is agrotourism area located in East Manggarai Regency. This research aims to analyze the strategy to improve the region. The research employs the qualitative method, in which the data is collected through observation, in-depth interviews, documentation, and Focus Group Discussion (FGD). The process and technique used are qualitative-descriptive and SWOT analysis. Typologically, the result showed that the attraction in Colol can be categorized into two types: agrotourism as the core attraction and nature, culture, history, and religion as the supporting attraction. Based on the tourism life-cycle perspective, the Colol valley region is considered at the exploration level, whereby there is no clear identification and inventory regarding tourism potential at the attraction level. In terms of the institutional level, there is no institution managing the tourism issue. At the stakeholder’s role level, the government plays an important role; meanwhile, the local community contributed less to developing the tourism sector. This circumstance indicates that the development of mass tourism-based is not well-applied in this region. The SWOT analysis shows the weaknesses and obstacles to the development of the Colol Valley Area including aspects of attractions, accessibility, amenities and ancillary. According to SWOT analysis, the development of Colol region can be analyzed as follows: First, the SO strategy (strength-opportunities) as an action to improve the product quality, the management of tourism destination, infrastructure development, amenity, as well as accessibility in obtaining the significant visitors to Labuan Bajo. Second, WO strategy (weakness-opportunities) as an action by strengthening the tourism institutional and the promotion of tourism destinations. Third, the ST (Strength-Threat) strategy is to maximize the existence potential by expanding the facilities and collaborative teamwork among stakeholders. Finally, the WT strategy (weakness- threat) is a development of human resources by conducting training that aims to fund independence-based besides government budgeting. The local government of East Manggarai Regency needs to configure a tourism governance system that is expected to be an instrument in managing and arranging the Colol region tourism development system, including creating a master plan. Therefore, this region is recommended for an acropolitan area with the support and collaborative action by all stakeholders such as, government, official institutions, and non- Government organizations. Keywords: colol valley region; SWOT analysis; development strategy